Factors affecting delivery and transient expression of β-glucuronidase gene in Dendrobium Sonia protocorm-like-body - Abdullah, Janna Ong; Mahmood, Maziah; Ghulam Kadir, Ahmad Parveez; Kadzimin, Salleh (Academic Journals, 2006)
The effect of the biolistic device parameters and other factors affecting delivery and expression of uidA gene in Dendrobium Sonia was investigated. Three week old protocorm like body (PLB) were mombarded with gold microparticles coated with pAHC25 plasmid harbouring the uidA gene which encodes β-glucuronidase. The factors investigated were the helium pressure, target distance, macrocarrier flight distance to stopping screen, distance from stopping screen to target tissues, vacuum pressure, gold microparticles size, spermidine and calcium on DNA precipitation, and the number of bombardments. Two days after bombardment, the PLB were subjected to histochemical GUS assay, and transient GUS activity was recorded as blue spots using a Leica streomicroscope. All the factors tested showed significant effects (p<0.05) on the delivery of DNA and expression of the uidA gene in Dendrobium PLB except for calcium. Surviving PLBs were able to grow and regenerate normally into plantlets.